56=-7y

Simple and best practice solution for 56=-7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56=-7y equation:


Simplifying
56 = -7y

Solving
56 = -7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7y' to each side of the equation.
56 + 7y = -7y + 7y

Combine like terms: -7y + 7y = 0
56 + 7y = 0

Add '-56' to each side of the equation.
56 + -56 + 7y = 0 + -56

Combine like terms: 56 + -56 = 0
0 + 7y = 0 + -56
7y = 0 + -56

Combine like terms: 0 + -56 = -56
7y = -56

Divide each side by '7'.
y = -8

Simplifying
y = -8

See similar equations:

| j-17+11+18-12=89 | | 250+2.8x=45 | | 2(15m+3)=3.5m-1 | | 10r=280 | | n+-8=-6 | | x^2-7x-17=-8x+3 | | 18s^2=50s | | 4x-8=82 | | 123=7x+5x+3 | | 3x^2-800=1400+2x^2 | | 2x(4+2)-9=15 | | 111111x+c-d=12 | | 2x-5x+5x= | | 125.6=9.42x^2+37.68x | | u-38=735 | | 18-5x=6-8x | | y+7=zfory | | x^2-7x+20=10 | | 13y+25x=38 | | 5-2x+7x=-10 | | (x-6-5i)(x-6+5i)=0 | | 5x-29=56 | | n+-14=-12 | | n^2=2.77 | | 42=3x+4x+7 | | 10x+60y=250 | | k+18=-25 | | 25/9=x/15 | | p/13=24 | | 7+x+x=31 | | 0.2x+x=240 | | 12(n+1.1)=96 |

Equations solver categories